A promise and a way of life : white antiracist activism - Thompson, Becky W. (University of Minnesota Press, 2001)
"A Promise and a Way of Life weaves an account of the past half-century based on the life histories of thirty-nine people who have placed antiracist activism at the center of their lives. Through a rich and intriguing narrative that links individual experiences with social and political history, Thompson shows the ways, both public and personal, in which whites have opposed racism during several social movements: the Civil Rights and Black Power movements, multiracial feminism, the Central American peace movement, the struggle for antiracist education, and activism against the prison industry